4. Triassic Magnetite and Diabase at Cornwall, Pennsylvania - Davis M. Lapham (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
Ore bodies at Cornwall, Pennsylvania, have been mined since 1742 principally for iron from magnetite, but also for copper (in chalcopyrite), silver (in chalcopyrite), gold (in chalcopyrite), cobalt (in pyrite), sulfur, and crushed limestone aggregate. Metallization occurs as a limestone replacement above the essentially conformable, south dipping portion of a discordant saucershaped diabase sheet. Pre-Triassic and Triassic faulting have emplaced host Cambrian limestone and two Ordovician(?) hornfels units, now for the most part resting above diabase. Thermal metamorphism of carbonate-bearing country rocks largely to calc-silicates, is ubiquitous. Metasomatism, particularly of potassium, is unique to ore zones. Associated magnetite- actinolite mineralization replaces, in a preferential sequence, all earlier metamorphic and metasomatic minerals and rarely diabase chilled margin. Mineralogical (diopside, actinolite, mica, sulfides, oxides) and chemical (Fe, Cu, S, Co) zoning of the eastern ore body is focused down dip, near its western edge, along a major vertical fault through diabase. This zoning is spatially related to magnetite veins in diabase, to an ore body within diabase, and to a shear zone that probably extends through the sheet.